Research methods for product design - Rodgers, Paul; Milton, Alex (London : Laurence King Publishing, 2013)
This title provides the reader with a comprehensive, relevant, and visually rich insight into the world of research methods specifically aimed at product designers. It includes practical case studies and tutorials that will inform, inspire and help you to conduct product design research better
What is product design research? -- Looking -- Learning -- Asking -- Making -- Testing -- Evaluation & selection -- Communicating
Includes bibliographical references (p. 182-185) and index
Keywords: Product design; Product design -- Research; Product design -- Research -- Methodology